Encyclopedia of modern Greek literature - Merry, Bruce (Gale virtual reference library, 2004)
Includes entries on important authors, texts, genres, themes, and topics in Greek literature from the Byzantine period to the present. Provides basic information on the history and development of modern Greek literature and language.